The Overview of Innovations in the Legal Framework and Organization of Correctional Service - Vilard Bytyqi; Fitore Morina (Hasanuddin Law Review, 2019)
The main institution in Kosovo that deals with the execution of criminal sanctions and it is Kosovo Correctional Service (KCS). Since its establishment, this institution has undergone numerous changes in the organizational field, as well as changes created by legal regulation. The recent trends occurring in correctional services in democratic societies have transformed these services in order to have a human approach and, in several cases constitute a decisive factor in the change in the behaviour of delinquents. Delinquents that have been convicted for serious crimes by criminal proceedings of final judgment, in order to rehabilitate through based programs on contents of rehabilitation, resettlement, and reintegration used a various method which will be treated in this paper. Considering legal changes which have occurred, these changes have affected executive bodies in charge of the execution of criminal sanctions. In this paper were applied several methods, such as individual case study, normative analysis, and qualitative methods. From the results of the treatment, we can see that through the legal changes made in this area of Correction have special importance. The correctional system as organized by the Correctional Service has advanced regarding the terms of legislation, influenced by the European system implemented in some countries in this field.